Development of a traffic emission inventory for a mexican city - Jaime, Aideé Morales (2012)
Air pollution has been one of the priorities issues in the environmental awareness, especially in cities from developing countries. Transport sector has an important contribution to the urban air quality degradation in these countries. Hence the importance to develop traffic emission inventories in order to allow the identification and quantification of atmospheric pollutant emissions in a defined area. The aim of this work is to develop a traffic emission inventory for the city of Querétaro, Mexico, using two different approaches (top-down and bottom-up) and to compare the results obtained from using both methodologies. Vehicle emissions from top-down inventory for the state of Querétaro show an increase compared to vehicle emissions reported in the 1999 Mexican National Emission Inventory due to the accelerated growth and development of the city of Querétaro. Emissions from the municipalities located in the south of the state of Querétaro are higher than in the rest of the municipalities, probably due to the higher number of highways and roads existing in this area. Vehicle emissions from bottom-up inventory using IVE model and considering different type of roads show that arterial roads are the main contributors of emission due to vehicle activity, followed by highways, second arterial roads, and local roads. The comparison of the two methodologies shows that CO emissions from bottomup inventory are higher than CO emissions from top-down inventory. One of the possible reasons for having this behaviour is due to the default parameters used by IVE model which might cause an overestimation of CO emissions. In order to have a better understanding of this difference further analysis of the default parameters used by IVE model should be considered. Local emission factors and traffic measurements are strongly recommended to be used in IVE model in order to improve vehicle emission estimations.